2014
DOI: 10.1071/an14329
|View full text |Cite
|
Sign up to set email alerts
|

Use of nitrate and Propionibacterium acidipropionici to reduce methane emissions and increase wool growth of Merino sheep

Abstract: The effects of dietary nitrate and of Propionibacterium acidipropionici (PA) on methane and nitrous oxide emissions, methaemoglobinaemia, volatile fatty acid (VFA) concentration and productivity of sheep were studied. It was hypothesised that PA supplementation would increase the rate of nitrite reduction to ammonia in the rumen and therefore reduce risks of methaemoglobinaemia. Fine-wool Merino wethers (n = 28; 31.8 ± 3.7 kg; 11 months of age) were acclimated to four isonitrogenous and isoenergetic diets base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 27 publications
5
19
1
1
Order By: Relevance
“…Higher levels of 10 to 20 mg N 2 O head −1 h −1 were reported for lactating dairy cows (Hamilton et al, 2010) and for feedlot steers and calves (Stackhouse et al, 2011). And in a recent study, de Raphélis‐Soissan et al (2014) reported that respiration chambers with sheep fed NO 3 − instead of urea had higher N 2 O emissions, thus lowering the GHG mitigation effect of CH 4 by 18%. These studies were all conducted with respiration chambers and the source(s) of N 2 O unknown.…”
mentioning
confidence: 99%
“…Higher levels of 10 to 20 mg N 2 O head −1 h −1 were reported for lactating dairy cows (Hamilton et al, 2010) and for feedlot steers and calves (Stackhouse et al, 2011). And in a recent study, de Raphélis‐Soissan et al (2014) reported that respiration chambers with sheep fed NO 3 − instead of urea had higher N 2 O emissions, thus lowering the GHG mitigation effect of CH 4 by 18%. These studies were all conducted with respiration chambers and the source(s) of N 2 O unknown.…”
mentioning
confidence: 99%
“…as major pathway and secondly, possibly being quantitatively less important, NO 3 − and NO 2 − being toxic to methanogens in the rumen. In both cases, CH 4 production was decreased by addition of nitrate, however, de Raphélis-Soissan et al [46] stated that, on the other hand, the N 2 O emission from sheep in respiration chambers was increased which led to a reduction of the net benefit of methane mitigation on global warming potential (CO 2 equivalents/kg DMI) of 18%. This effect could be mitigated by using encapsulated NO 3 − as slow-release form, thereby lowering NO 2 − toxicity after nitrate ingestion [11].…”
Section: Concentration Ratios In the Rumenmentioning
confidence: 99%
“…However, only traces were found under those experimental feeding conditions with addition of nitrate. Also de Raphélis-Soissan et al [46] and Lee et al [11] fed nitrate to ruminants in an attempt to lower ruminal CH 4 production. In this regard, two main possibilities by which NO 3 − reduces enteric CH 4 production were discussed [11]: NO 3 − reduction (thermodynamically favorable in comparison to methanogenesis)…”
Section: Concentration Ratios In the Rumenmentioning
confidence: 99%
See 1 more Smart Citation
“…Como em outros estudos ( VAN ZIJDERVELD et al, 2010;RAPHÉLIS-SOISSAN et al, 2014;GUYADER et al, 2015;LEE et al, 2015a) alimentos concentrados o pico de produção é 2 a 3 horas após a ingestão e para alimentos volumoso 4 a 5 horas. Contudo, neste experimento a menor proporção de acetato (mol %), em ambas as dietas foi observada 4 horas após a alimentação coincidindo, com a redução no pH…”
Section: Discussionunclassified